Mithras Sol (Archaeologia Adriatica, 2007)
The worship of Sol and solar cults was deeply rooted in Rome. In the late Republican and early Imperial periods the popularity of solar cults was minimal, except during the reigns of those emperors who were propagators of solar deities. Sol as a personal deity was important in the promotion of the imperial cult, as well as in proving divine origins, for the restoration of the mythic golden age, in confirmation of earthly governing under celestial patronage, and finally in apotheosis and deification. Heliolatry would decline with the removal of individual emperors. Imported Greek, Oriental, and Egyptian components from various religious, philosophical, and astrological sources influenced the development of the cult and iconography of Sol. Aurelian created a new supreme god from local, minor, and provincial deities, who played an important role in the Roman religion of the third and fourth centuries. The article emphasizes the diversely composed characters of the solar deities worshipped in Rome, which are compared with the Mithraic Sol at three levels: mythological, cosmogonical, and liturgical.In Mithaism, the role of Sol had already been determined during the course of the 1st century, and from the very beginning it was of great importance. Sol appears in numerous episodes of narratives depicting Mithras. His position in iconographic images featuring bull sacrifice indicates that he had a subordinate role in relation to Mithras, but these two figures are shown as equals in important images of the mythic banquet. Illustrations of stories about Mithras have acquired complicated theological interpretations. Attempts to utilize mythic cosmogonical episodes to explain the cosmic order, mean that the central Mithaic image, the sacrifice of the bull, can also be understood as an astral map. The figures from myth have their celestial counterparts in the stars and planets located in the heavenly circles – the equator and the eclipse. The heavenly counterpart of Mithras in the bull sacrifice is the Sun, particularly when it is in the constellation of Leo during the summer solstice. Mithras is the controller of all constellations and processes, he kills the astral Bull, and thus begins the cycle of the incarnation of souls. The cosmic role of Sol is the return of the soul from corporality and its elevation back into the astral sphere. The planetary deities and lesser demons are those that control the various stages in this process. Mithraism in fact affirmed this vertical ascent, in which Sol had the role of a psychopomp, as he could raise steam, and hence souls, who were held to be a breath, a vapour, something airy, light, and moist. Sol becomes an angel – a mediator between the human and divine.Mithras and Sol are always shown as separate entities in the depictions of legends. The differences are emphasized through the iconography. An exclusive attribute of Sol is the radial crown. However, on votive inscriptions Mithras is invocated as Sol Invictus, and in scenes of petrogenesis, he is born from lifeless stone holding in his hands a knife (later used to kill the bull) and a torch (and attribute of Sol). This suggests the possibility that in theology the two figures could have been conceived as two expressions of one solar being – perhaps the Sun by night (Mithras) and day (Sol), but it is equally likely that the intention was to emphasize the opposition of these figures.
Keywords: Sol; Mithras; mythic feast; petrogenesis; bull sacrifice (tauroctonia); celestrial maps; psyhopomp